Beyond resources: declining parental requests for futile treatment - Wilkinson, D (Lancet, 2017)
The sad and difficult case of Charlie Gard, is the latest in a series of court cases in the UK when parents and doctors have disagreed about medical treatment for a child. Doctors regard the treatment as “futile” or “potentially inappropriate”. Parents, in contrast, want treatment to continue. In the current case, the judge rejected Charlie’s parents’ request for him to travel to the US for an experimental medical treatment. He ruled that life-sustaining treatment could be withdrawn, and Charlie allowed to die. When doctors and the courts consider cases like this one, they often focus exclusively on best interests. In some cases, however, it is uncertain whether or not treatment would be in the interests of the patient. Indeed, there may be stronger and clearer arguments to limit treatment on the basis of finite and scarce medical resources.